A Teaching Note: Using Games To Bring A Classroom To Life - Ganoe, Yvette; Bryant, Douglas (Teaching History: A Journal of Methods, 2011)
For decades teachers across the United States have used games as instructional tools. Games provide many benefits to the learning experience. Well-structured gaming lessons increase student immersion into the content, create powerful visual memories of that content, and raise the "fun factor" for a given unit of study. For another benefit, games work with different types of student learners, blending auditory, visual, and kinesthetic (hands-on) opportunities for students to approach and master a subject. When teachers embed games into their classes, they can be useful teaching techniques at any academic level. This teaching note describes the use of a war game at the secondary level, but teachers also can use games with great effectiveness in college history classes.